PEMBUATAN MI JAGUNG KERING DENGAN METODE KALENDERING [Corn Noodle Processing using Calendaring Method] - . Subarna; Tjahja Muhandri (Jurnal Teknologi dan Industri Pangan, 2013)
The objective of this research was to investigate the effect of extrusion and drying conditions on the corn noodle and processing using calendaring method. Corn flour (70%) was steamed, mixed with raw corn flour (30%), added with water (50%), salt (1%) and guar gum (1%). Treatment applied before sheeting were control (without extrusion), extrusion using 0.60 cm die diameter and using 0.30 cm die diameter. Noodle strands from the best extrusion treatment were dried in the tray dryer at 60, 70 and 80ºC. Extrusion of dough using grinder increased its degree of gelatinization. Without extrusion before sheeting, the dough was too hard to form a smooth sheet and the resulting noodle strand was fragile. Smaller die diameter (0.30 cm) resulted in lower cooking loss, stickiness and elasticity of corn noodle produced (p<0.05), but noodle toughness and elongation were not significantly different. Corn noodles dried at 60ºC for 40 minutes had longer elongation (p<0.05), but the cooking loss, toughness, and stickiness were not significantly different (p>0.05).